Tropical architecture - Kukreja, C. P. (New Delhi, India : Tata McGraw-Hill Publishing Company Limited, 1978)
The design and construction of human dwellings and settlements in a region are influenced, besides other factors, to a great extent by the climate and physical environment of the region. In constructing shelters for himself over the centuries, man has always taken into consideration these factors, sometimes consciously in a systematic way.
1. Man, shelter and climate -- 2. Climatic elements -- 3. Comfort zone and bioclimatic chart -- 4. Sun and the design process -- 5. Orientation and town planning -- 6. Ventilation -- 7. Building materials -- 8. Landscaping -- 9. Cooling devices -- 10. Design analysis.
Includes bibliographical references.
Keywords: ARCHITECTURE -- TROPICAL